Study of the thermal behavior of Al(III) and In(III)-diclofenac complexes in solid state - Kobelnik, Marcelo [UNESP]; Cassimiro, Douglas Lopes [UNESP]; de Almeida, Adelia Emilia [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Crespi, Marisa Spirandeli [UNESP] (Springer, 2011)
The Al and In-diclofenac compounds were prepared. Thermogravimetry (TG) and X-ray diffraction powder patterns were used to characterize these compounds. Details concerning the dehydration and thermal decomposition as well as data of kinetic parameters have been described here. The kinetic studies of these stages were evaluated from several heating rates with mass sample of 2 and 5 mg in open crucibles under nitrogen atmosphere. The results of the present study improve the knowledge on these compounds including their dehydration and thermal stability. The obtained data leads to a dependence on the sample mass, which results in two kinetic behavior patterns.
Keywords: Diclofenac; Dehydration; Thermal decomposition; Kinetic parameters